BRANDERPRENEURSHIP FRAMING ANALYSIS: A Methodological Framework - Wijaya, Bambang Sukma (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
Entrepreneurship and branding have an intersection on the desire for innovation. Therefore, Branderpreneurship, as a concept of brand development-based entrepreneurship, focuses on the added values resulted from continuous innovation. This article highlights the methodological aspects of branderpreneurship in appraising the extent to which brand development-based entrepreneurship performs in innovating brand values in an atmosphere of business competition and excellent communication. Two methodological approaches use Branderpreneurship Framing Analysis (BFA), both qualitatively and quantitatively. Qualitative BFA (ql.BFA) focuses on the study of strategic business performance to develop brands through the lens of the circle of values development in Branderpreneurship theory, which includes the dimensions of identifying, creating, delivering, communicating, maintaining, evaluating, and updating values. Quantitative BFA (qt.BFA) focuses on measuring the performance scale in each dimension by referring to the values 0-1 (bad), 1-2 (good), and 2-3 (excellent). This method is beneficial for assessing the Branderpreneurship performance of SME brands and start-up businesses.   BRANDERPRENEURSHIP FRAMING ANALYSIS: Sebuah Kerangka Metodologis Kewirausahaan dan branding memiliki titik singgung pada hasrat akan inovasi. Karena itu, branderpreneurship, sebagai konsep kewirausahaan berbasis pengembangan merek, fokus pada nilai tambah yang dihasilkan dari inovasi yang tiada henti. Artikel ini menyoroti aspek metodologis dari branderpreneurship dalam mengukur sejauh mana strategi kewirausahaan berbasis pengembangan merek berhasil dalam menginovasi nilai-nilai merek di tengah atmosfer persaingan bisnis dan komunikasi yang ketat. Dua pendekatan metodologis menggunakan Branderpreneurship Framing Analysis (BFA), baik secara kualitatif maupun kuantitatif. Qualitative BFA (ql.BFA) fokus pada kajian performa strategis sebuah usaha dalam upaya pengembangan merek melalui kacamata the circle of values development dalam teori Branderpreneurship yang mencakup dimensi-dimensi identifying, creating, delivering, communicating, maintaining, evaluating, dan updating values. Quantitative BFA (qt.BFA) fokus pada pengukuran skala performa di setiap dimensi dengan merujuk pada nilai 0-1 (buruk), 1-2 (baik), dan 2-3 (sangat baik). Metode ini sangat berguna untuk menilai performa branderpreneurship merek-merek UKM (Usaha Kecil dan Menengah) dan usaha-usaha rintisan.  To cite this article (7th APA style): Wijaya, B. S. (2014). Branderpreneurship Framing Analysis: A Methodological Framework. Journal Communication Spectrum, 4(2), 156-169